Sistem Informasi Administrasi Perkantoran pada Badan Kesatuan Bangsa dan Politik Kabupaten Banggai Kepulauan - Sukmawati Sukmawati; Marwan M. Londol; I Gusti Putu Rika Permana; Agustince A. Lesak4; Trisno Wibowo. K (Pusat Riset dan Inovasi Nasional, 2025)
Correspondence administration is one of the vital aspects in supporting the effectiveness of communication, coordination, and documentation in the government environment. In the context of the Banggai Islands Police Department, the letter administration function has a strategic role because this institution is tasked with coordinating political affairs and fostering national insight which requires a fast, precise, and well-documented flow of information. However, facts in the field show that the mail administration process is still carried out manually, so it is prone to causing various problems. Some of the main obstacles that arise include the risk of losing documents, delays in distributing information, and difficulties in finding and searching for urgently needed mail archives. This condition has the potential to hinder the smooth running of services and reduce the quality of public administration governance. This research aims to design and build an integrated digital-based mail administration information system, in order to answer these challenges. The methodology used includes analyzing user needs, system design, application implementation, and testing stages to ensure system performance runs according to expectations. With the digitization of the mail administration process, it is hoped that it can increase efficiency in recording and distributing documents, speed up archive searches through structured databases, and present accurate and transparent reports. The results of this research are expected to be able to make a real contribution to bureaucratic modernization efforts, especially in the Banggai Islands Police Department. The information system developed not only simplifies document governance, but also supports the principles of accountability, transparency, and public services that are more responsive to the needs of the community. Thus, the implementation of this system is expected to be a strategic step in realizing a more professional and information technology-based government administration.